PENGARUH KEMUNGKINAN TERDETEKSINYA KECURANGAN, KECENDERUNGAN PERSONAL, DAN TEKNOLOGI SISTEM PERPAJAKAN TERHADAP TAX EVASION (STUDI KASUS PADA WAJIB PAJAK HOTEL YANG TERDAFTAR DI BP2D KOTA MALANG) - Chandry Dyah Ratsminassiwi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The objective of this research is to assess and to analyze the effect of fraud detection possibility, tax payer’s personality, and taxation system technology on tax evasion committed by hotel business in Malang. Tax evasion is an illegal action of avoiding tax imposition and action of breaking tax regulation. There is a chance that tax evasion can inflict a financial loss for the goverment due to lower hotel tax contributions. The primary data of this study were collected through questionnaires distributed to 83 hotel taxpayers registered at the Local Tax Service Office (BP2D) in Malang. The sampling method used in this research is judgment-type purposive sampling. The hypothesis was analyzed using Statistical Product and Service Solutions (SPSS). The result of this research shows that fraud detection possibility is not significant in influencing hotel tax evasion in Malang. On the contrary, tax payer’s personality and taxation system technology signifcantly influence hotel tax evasion in Malang, where the former factor plays the most influential part.Keywords: Hotel Taxpayers, Fraud, Tax Payers’ Personality, Taxation System Technology, Tax Evasion